2022
DOI: 10.1038/s41598-022-18757-w
|View full text |Cite
|
Sign up to set email alerts
|

Analytical techniques for mapping multi-hazard with geo-environmental modeling approaches and UAV images

Abstract: The quantitative spatial analysis is a strong tool for the study of natural hazards and their interactions. Over the last decades, a range of techniques have been exceedingly used in spatial analysis, especially applying GIS and R software. In the present paper, the multi-hazard susceptibility maps compared in 2020 and 2021 using an array of data mining techniques, GIS tools, and Unmanned aerial vehicles. The produced maps imply the most effective morphometric parameters on collapsed pipes, gully heads, and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…The use of "UAVs" in natural events and urgent situations is developing (Watson et al, 2019;Windrim et al, 2019), and compared to conventional tools, it has the potential to prepare data with better resolution (Brovkina et al, 2018). Recently "UAV" was applied in multi-hazard susceptibility mapping in the same hilly loess region of the current study by Kariminejad et al (2022) where they reported sinkholes were the most perilous natural hazard, followed by landslides, and headcuts. UAVs have been used on several papers to collect various data for landslide inventories, and piping/headcut monitoring (Lin et The literature indicates that there are few studies that examine the use of UAV with DL to automatically map landslides and sinkholes, while none of them is tested in a semi-arid environment.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…The use of "UAVs" in natural events and urgent situations is developing (Watson et al, 2019;Windrim et al, 2019), and compared to conventional tools, it has the potential to prepare data with better resolution (Brovkina et al, 2018). Recently "UAV" was applied in multi-hazard susceptibility mapping in the same hilly loess region of the current study by Kariminejad et al (2022) where they reported sinkholes were the most perilous natural hazard, followed by landslides, and headcuts. UAVs have been used on several papers to collect various data for landslide inventories, and piping/headcut monitoring (Lin et The literature indicates that there are few studies that examine the use of UAV with DL to automatically map landslides and sinkholes, while none of them is tested in a semi-arid environment.…”
Section: Introductionmentioning
confidence: 89%
“…Landslides have also endangered the residents of the study area and their properties. Since these geohazards are rainfall-induced, they increase in size and severity after erosive rainfall (Kariminejad et al, 2022). Therefore, these issues, apart from identifying the factors in uencing the formation of these land degradation processes, led us to restate the problems and their impacts to nally nd suitable solutions for their management.…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations
“…They offer advantages such as low manufacturing costs, high portability, and suitability for extreme environments. With the rapid advancement of UAV technology, their applications have expanded from initial military applications, such as patrol reconnaissance and small-scale combat, to civilian domains, including route inspections and high-altitude mapping [2]. The widening scope of applications introduces increasing complexity in situations where UAVs encounter obstacles.…”
Section: Introductionmentioning
confidence: 99%